2021
DOI: 10.1101/2021.02.08.430238
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Quantitative proteomics identifies secreted diagnostic biomarkers as well as tumor-dependent prognostic targets for clear cell Renal Cell Carcinoma

Abstract: Clear cell Renal Cell Carcinoma (ccRCC) is the third most common and most malignant urological cancer, with a 5-year survival rate of 10% for patients with advanced tumors. Here, we identified 10,160 unique proteins by in-depth quantitative proteomics, of which 955 proteins were significantly regulated between tumor and normal adjacent tissues. We verified 4 putatively secreted biomarker candidates, namely PLOD2, FERMT3, SPARC and SIRPα, as highly expressed proteins that are not affected by intra- and inter-tu… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 61 publications
(48 reference statements)
0
2
0
Order By: Relevance
“…Many biomarkers have been found to be useful for the early diagnosis or long-term prognosis of patients with RC, such as mutation rates of VHL and PBRM1 in somatic cells, urine proteomics detection, and immune detection points (46)(47)(48). As a recent hot topic in tumor development, the role of noncoding RNA (ncRNA) in RC has been gradually explored (49).…”
Section: Discussionmentioning
confidence: 99%
“…Many biomarkers have been found to be useful for the early diagnosis or long-term prognosis of patients with RC, such as mutation rates of VHL and PBRM1 in somatic cells, urine proteomics detection, and immune detection points (46)(47)(48). As a recent hot topic in tumor development, the role of noncoding RNA (ncRNA) in RC has been gradually explored (49).…”
Section: Discussionmentioning
confidence: 99%
“…Forkhead box M1, the epithelial-mesenchymal transition-related gene, can be used as a prognostic biomarker. The NADH dehydrogenase (ubiquinone) 1 alpha subcomplex, 4-like 2 can be used as an invasive marker ( 99 101 ). Applying bioinformatics technology to tumor studies has even shown explosive growth in recent years ( 102 105 ).…”
Section: Emerging Potential Therapeutic Approachesmentioning
confidence: 99%